The impacts of severe perfusion defects, akinetic/dyskinetic segments, and viable myocardium on the accuracy of volumes and LVEF measured by gated 99mTc-MIBI SPECT and gated 18F-FDG PET in patients with left ventricular aneurysm: cardiac magnetic resonance imaging as the reference - Wei, Hongxing; Tian, Congna; Schindler, Thomas H.; Qiu, Mei; Lu, Minjie; Shen, Rui; Tian, Yueqin; Zhao, Shi-hua; Zhang, Xiaoli (Journal of nuclear cardiology, 2014)
To compare the accuracy of end-diastolic and end-systolic volumes (EDV, ESV) and LV ejection fraction (LVEF) measured by both GSPECT and GPET, using cardiac magnetic resonance imaging (CMR) as a reference. Furthermore, the impacts of severe perfusion defects, akinetic/dyskinetic segments, and residual viable myocardium on the accuracy of LV functional parameters were investigated. Ninety-six consecutive patients with LV aneurysm and LV dysfunction (LVEF 32 ± 9%) diagnosed by CMR were studied with GSPECT and GPET. EDV, ESV, and LVEF were calculated using QGS software. Correlations of volumes were excellent (r 0.81-0.86) and correlation of LVEF was moderate (r 0.65-0.76) between GSPECT vs CMR and between GPET vs CMR. Compared with CMR, ESV was overestimated by GSPECT (P < .01) and underestimated by GPET (P < .0001); EDV was underestimated by GPET (P < .001); LVEF was underestimated by GSPECT but overestimated by GPET (both P < .001). Multivariate regression analysis revealed that the number of segments with severe perfusion defects (P < .001) was the only independent factor which was correlated to the EDV difference between GSPECT and CMR, the number of akinetic/dyskinetic segments with absent wall thickening (WT) was the only independent factor which was significantly correlated to the differences of ESV and LVEF measurements between GSPECT vs CMR and between GPET vs CMR (P < .0001), respectively. Neither the mismatch score nor the segments with viable myocardium were correlated to the differences of LV volumes and LVEF measurements between different imaging modalities. In LV aneurysm patients, LV volumes and LVEF measured by both GSPECT and GPET imaging correlated well with those determined by CMR, but should not be interchangeable in individual patients. The accuracy of LVEF measured by GSPECT and GPET was affected by the akinetic/dyskinetic segments with absent WT.